Serum matrix metalloproteinase 7 (MMP7) is a biomarker of fibrosis in patients with non-alcoholic fatty liver disease - Katharine M. Irvine (Nature Portfolio, 2021)
Abstract Non-alcoholic fatty liver disease (NAFLD) affects 25% of the adult population globally. Since liver fibrosis is the most important predictor of liver-related complications in patients with NAFLD, identification of patients with advanced fibrosis among at-risk individuals is an important issue in clinical practice. Transient elastography is the best evaluated non-invasive method used in referral centres to assess liver fibrosis, however serum-based tests, such as the Enhanced Liver Fibrosis (ELF) score, have a practical advantage as first-line tests due to their wider availability and lower cost. We previously identified matrix metalloproteinase 7 (MMP7) as a serum biomarker of histological advanced fibrosis in a mixed-etiology patient cohort. In this study we aimed to determine the association between MMP7 and fibrosis, assessed by transient elastography, in patients with NAFLD. Serum MMP7 levels were measured in a cohort of 228 patients with NAFLD. Associations between MMP7, liver stiffness measurement (LSM), ELF score and clinical parameters were determined using logistic regression modelling. Serum MMP7 was associated with clinically significant fibrosis (LSM ≥ 8.2), independent of age, gender, BMI and diabetes. The addition of MMP7 significantly improved the diagnostic performance of the ELF test, particularly in patients over the age of 60. Combinations of serum biomarkers have the potential to improve the sensitivity and specificity of detection of advanced fibrosis in at-risk patients with NAFLD. We have demonstrated that serum MMP7 is independently associated with clinically significant fibrosis and improves the diagnostic performance of currently available tests in older patients.